THE IMPACT OF GADGET USE ON COGNITIVE DEVELOPMENT OF STUDENTS - Rifqi, Muhammad Ichsan; Suwendi, Suwendi (Idaarah: Jurnal Manajemen Pendidikan, 2025)
Excessive use of gadgets can hurt its users, especially in cognitive development. This study analyses the negative influence of gadget use on the cognitive development of students at MTs Al Muchtari IBS by considering their gadget use patterns during their elementary school years. This study uses a qualitative approach with a field research method. The results show that students with the highest academic achievement tend not to use gadgets excessively during learning activities at school. They utilize gadgets as tools to understand assignments, review ununderstood materials, and have good self-regulated learning skills. In contrast, students with the lowest academic achievement use gadgets more often at school, including in doing assignments, but have low self-control. Parents and teachers are very important in supervising gadget use to prevent student gadget addiction. In addition, it is necessary to design activities that do not involve gadgets and strengthen self-regulated learning skills so that students can control gadget use more effectively.